1996
DOI: 10.1093/ajcp/106.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Nuclear Segmentation in Mild Cobalamin Deficiency:Relation to Metabolic Tests of Cobalamin Status and Observations on Ethnic Differences in Neutrophil Segmentation

Abstract: Neutrophil hypersegmentation is considered the most sensitive peripheral blood cell marker of cobalamin deficiency. However, its diagnostic value in the mild deficiency states that accompany most low cobalamin levels and its relation to metabolic tests of cobalamin status are unknown. The authors compared neutrophil lobe averages and percent neutrophils with 5 or more lobes (%5+ lobes) in 169 subjects with their mean corpuscular volume (MCV) and serum cobalamin, methylmalonic acid (MMA), homocysteine, and fola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…In a subgroup of our patients in which peripheral blood smears were examined, the presence of 6-lobed neutrophils seemed to be a very insensitive, nonspecific sign of early cobalamin deficiency. In a recent study, similar results have been reported for neutrophil lobe average and presence of 5 or more lobes [31].…”
Section: Discussionsupporting
confidence: 84%
“…In a subgroup of our patients in which peripheral blood smears were examined, the presence of 6-lobed neutrophils seemed to be a very insensitive, nonspecific sign of early cobalamin deficiency. In a recent study, similar results have been reported for neutrophil lobe average and presence of 5 or more lobes [31].…”
Section: Discussionsupporting
confidence: 84%
“…All are designed to establish, as efficiently and economically as possible, what the cause of the anemia is and to institute appropriate treatment wherever possible. 7,51 …”
Section: Resultsmentioning
confidence: 99%
“…This concurs with most reports in the literature stating that the presence of hypersegmented neutrophils on the peripheral blood smear is neither sensitive nor specific for this purpose. 15 However, careful review of a peripheral blood smear by a hematologist or hematopathologist may provide helpful clues regarding the underlying cause of a macrocytic anemia.…”
Section: Discussionmentioning
confidence: 99%